Evaluation of Sensitivity and Specificity of ELISA and PBA for IgM Detection to LPS Antigen of Salmonella Typhi - Helmy Widyastuti (Jurnal Ilmu Alam dan Lingkungan, 2018)
The high prevalence of typhoid fever in developing countries, includingIndonesia has prompted the exploration of various serologic tests and antigen detectionmethod to obtain an early and accurate diagnosis of patients with typhoid fever.Although typhoid fever is confirmed by culture of Salmonella enterica serotype Typhi,there is still an urgent need for the rapid, simple serological tests and evaluation ofeffective and appropriate diagnostics for typhoid fever. In this study, we evaluated and compared the sensitivity and specifity of ELISA and Passive Bacterial Agglutination(PBA) as an agglutination-based serological test to LPS antigen of Salmonella Typhiand the effectiveness of local antigen in detecting the production of specific antibody(IgM) to patient with typhoid fever. We collected serum sample of 50 suspected typhoidfever from DR. Wahidin Sudirohusodo General Hospital, Daya General Hospital, GowaGeneral Hospital and Kassi-Kassi Public Health Center in Makassar, South of Sulawesi.They were grouped based on sex, duration of fever, and age. Serum antibody titer weremeasured by ELISA and PBA. Data were analiyzed satistically by using cross tabulationand chi-square (CI = 95%). The Result of this study showed that PBA technique has thelevel of sensitivity and specifity respectively 100% and 92 %, while ELISA was 84% and28%. It suggested that PBA has a greater level of sensitivity and specifity than ELISA.We also showed that LPS antigen that we obtained from local isolate of SalmonellaTyphi, can be used as a standard antigen in diagnosing typhoid fever.